1988
DOI: 10.1093/nar/16.15.7233
|View full text |Cite
|
Sign up to set email alerts
|

Molecular consequences of truncations of the first exon forin vitrosplicing of yeast actin pre-mRNA

Abstract: A defined minimum length of the first exon is required for the generation of spliced products from a synthetic yeast actin mRNA-precursor in vitro. If the first exon is 1, 2, 3 or 5 nucleotides long, only the first step of the splicing reaction can take place. A transcript starting with the first nucleotide of the intron does not get converted into any of the normally obtained splicing products or intermediates. On the other hand, spliceosome assembly does not depend on the presence of a first exon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Yet, most of these 5Ј exon interactions are clearly dispensable for splicing in vitro. In both yeast and human splicing extracts, no decrease in first-step splicing efficiency is observed when the 5Ј exon is truncated to 2 nt, and even a 1-nt exon can support some lariat formation (Duchene et al 1988;Hertel and Maniatis 1999). In our hands, an AdML substrate with a 6-nt 5Ј exon underwent efficient lariat formation, but was significantly impaired for exon ligation (data not shown).…”
Section: Protection Of the 5ј Exon Intermediate Is Extensivementioning
confidence: 57%
See 1 more Smart Citation
“…Yet, most of these 5Ј exon interactions are clearly dispensable for splicing in vitro. In both yeast and human splicing extracts, no decrease in first-step splicing efficiency is observed when the 5Ј exon is truncated to 2 nt, and even a 1-nt exon can support some lariat formation (Duchene et al 1988;Hertel and Maniatis 1999). In our hands, an AdML substrate with a 6-nt 5Ј exon underwent efficient lariat formation, but was significantly impaired for exon ligation (data not shown).…”
Section: Protection Of the 5ј Exon Intermediate Is Extensivementioning
confidence: 57%
“…A 14-nt 5Ј exon did undergo exon ligation, but not as efficiently as longer sequences (data not shown). Similarly, efficient exon ligation in S. cerevisiae extracts requires the 5Ј exon to be somewhere between 6 and 12 nt (Duchene et al 1988). Thus, at least in vitro, truncation of the 5Ј exon is of little or no consequence for the first step of splicing, but there is a minimum 5Ј exon length requirement for the second step.…”
Section: Protection Of the 5ј Exon Intermediate Is Extensivementioning
confidence: 99%
“…To investigate the function(s) of the EJC apart from any other possible effects of pre‐mRNA splicing on mRNA metabolism, we wanted to generate mRNAs that had been produced by splicing but did not carry the complex. It was previously reported that pre‐mRNAs having a 5′ exon as short as 12 nt can support both steps of splicing in vitro (Duchene et al ., 1988; Chanfreau et al ., 1999). Since the EJC is deposited on spliced mRNAs >20 nt upstream of the 3′ end of the 5′ exon, we hypothesized that spliced mRNAs with 5′ exons <20 nt might not carry the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Neither sequence substitution caused a significant change in trans-splicing efficiency ( Figure 3B). Domdey and coworkers (Duchenne et al, 1988) showed in a yeast system that constructs containing first exons of 1, 2, 3 or 5 nucleotides participated only in the first step of splicing and did not participate in the second step. This mutation caused a modest reduction (30%) in utilization of the SL RNA, but as with the C25C26A27A28 mutation in stem I, the reduction in utilization was directly correlated with inefficient assembly of the shortened SL RNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%